Peran Pemerintah Dalam Penertiban Dan Penataan Tempat Hiburan Malam Di Kota Makassar - Patabo, Aras Putra Bula; Tahir, Muh; Rahim, Samsir (Universitas Muhammadiyah Makassar, 2021)
The purpose of this study was to determine how the government's efforts in controlling and structuring night entertainment venues in Makassar City. This study used a qualitative descriptive that intended to describe the role of government in controlling and structuring night entertainment venues in the city of Makassar. The number of informants in this study was 11 people, the data source consisted of primary data and secondary data obtained through interviews, while secondary data from documents, records, reports and official archives that could be supported by completeness of data primary. The results showed that the role of the government in controlling and structuring night entertainment venues in the city of Makassar had been running well according to the applicable procedures. Control of government arrangement in this matter had provided assistance to owners of night entertainment venues, including in providing assistance. Keywords: Role of Government, Order and Arrangement of Night Entertainment Venues